2010
DOI: 10.1038/nmat2799
|View full text |Cite
|
Sign up to set email alerts
|

A multiferroic material to search for the permanent electric dipole moment of the electron

Abstract: We describe the first-principles design and subsequent synthesis of a new material with the specific functionalities required for a solid-state-based search for the permanent electric dipole moment of the electron. We show computationally that perovskite-structure europium barium titanate should exhibit the required large and pressure-dependent ferroelectric polarization, local magnetic moments and absence of magnetic ordering at liquid-helium temperature. Subsequent synthesis and characterization of Eu(0.5)Ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
79
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 47 publications
5
79
1
Order By: Relevance
“…13 Nearly four decades ago, D. L. Janes et al 14 suggested that the solid solution Eu 0.5 Ba 0.5 TiO 3 would be simultaneously ferroelectric and ferromagnetic. In recent experiments, K. Z. Rushchanskii et al 15 found ferroelectric hysteresis loop around 130 K and antiferromagnetism below T N = 1.9 K in the same composition. While H. Wu et al 16 investigated theortically the intrinsic coupling between magnetism and dielectric properties in Eu 1-x Ba x TiO 3 (0 ≤ x ≤ 0.2), T. Wei et al 17 reported dielectric constant and electrical polarization in polycrystalline samples (0 ≤ x ≤ 1).…”
Section: Introductionmentioning
confidence: 94%
“…13 Nearly four decades ago, D. L. Janes et al 14 suggested that the solid solution Eu 0.5 Ba 0.5 TiO 3 would be simultaneously ferroelectric and ferromagnetic. In recent experiments, K. Z. Rushchanskii et al 15 found ferroelectric hysteresis loop around 130 K and antiferromagnetism below T N = 1.9 K in the same composition. While H. Wu et al 16 investigated theortically the intrinsic coupling between magnetism and dielectric properties in Eu 1-x Ba x TiO 3 (0 ≤ x ≤ 0.2), T. Wei et al 17 reported dielectric constant and electrical polarization in polycrystalline samples (0 ≤ x ≤ 1).…”
Section: Introductionmentioning
confidence: 94%
“…Recently, it was theoretically predicted that EuTiO 3 has antiferrodistorted ground state. 5,6 Experimental studies show that at room temperature the crystal structure is cubic P m3m perovskite, 7 which transforms to tetragonal I4/mcm structure near 280 K.…”
Section: Introductionmentioning
confidence: 99%
“…Within the recent decades, several technological innovations disrupted the rare-earth market [2], in turn stimulating the scientific quest for future materials. One vibrant field is the study of Eu 2+ compounds whose complex crystal structures are coupled with application-relevant properties including, to name only some recent examples, luminescence [3][4][5][6], field-induced reversal of the magnetoresistive effect [7], and complex magnetism [8,9]. The most renowned magnetic compounds are the europium chalcogenides that are considered ideal 3D Heisenberg systems [10].…”
Section: Introductionmentioning
confidence: 99%